2021
DOI: 10.3390/cancers13061407
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectral Signatures of Serum-Derived Extracellular Vesicle-Enriched Isolates May Support the Diagnosis of CNS Tumors

Abstract: Investigating the molecular composition of small extracellular vesicles (sEVs) for tumor diagnostic purposes is becoming increasingly popular, especially for diseases for which diagnosis is challenging, such as central nervous system (CNS) malignancies. Thorough examination of the molecular content of sEVs by Raman spectroscopy is a promising but hitherto barely explored approach for these tumor types. We attempt to reveal the potential role of serum-derived sEVs in diagnosing CNS tumors through Raman spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 79 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…, to assess their purity or for diagnostic purposes. 10,35–43 While confocal Raman spectroscopy involves the global analysis of the mean properties of a large number of vesicles, TERS may enable the investigation of single EVs with high spatial resolution, e.g. , to identify domains and specific fingerprint areas to be used as biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…, to assess their purity or for diagnostic purposes. 10,35–43 While confocal Raman spectroscopy involves the global analysis of the mean properties of a large number of vesicles, TERS may enable the investigation of single EVs with high spatial resolution, e.g. , to identify domains and specific fingerprint areas to be used as biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported a method to isolate small EVs from the extracellular matrix (ECM) of post-mortem human frontal cortex (13, 15, 18). The vesicles contain the hallmarks of endosomal derived exosomes (13, 15) and fulfilled the experimental requirements of the International Society for Extracellular Vesicles 2018 guidelines (19).…”
Section: Resultsmentioning
confidence: 99%
“…While there have been several studies on GBM derived EVs, only a few have been conducted on MNG derived EVs (79, 18, 50, 51). A study by Ricklefs et al (2022) observed that the levels of circulating EVs in the blood of meningioma patients are increased, correlating with malignancy grade and oedema, but subsequently declined post-surgery (8).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, analysis of the whole EV molecular pattern of the whole EV set would provide more relevant results. This approach has recently been applied in clinical studies for tumor diagnostic purposes [142][143][144].…”
Section: Discussionmentioning
confidence: 99%